A fast and simple branching algorithm for solving small scale fixed-charge transportation problem - Krzysztof Kowalski; Benjamin Lev; Wenjing Shen; Yan Tu (Operations Research Perspectives, 2014)
In this paper, we develop a simple algorithm for obtaining the global solution to a small scale fixed-charge transportation problem (FCTP). The procedure itself is very quick. The proposed method solves FCTP by decomposing the problem into series of smaller sub-problems, which is novel and can be useful to researchers solving any size of the problem.
Keywords: 330; Transportation problem; Fixed charge; Branching method